Plasma properties in eruptive prominences. Issue Volume 8:Issue S300(2013) (6th January 2014) - Labrosse, Nicolas
Abstract: Prominence eruptions are one of the most spectacular manifestations of our Sun's activity. Yet there is still some mystery surrounding their relevant physical conditions. What are their plasma parameters? How different are they from those of quiescent prominences? How do they relate to those within coronal mass ejections? We briefly review some recent results in non-LTE radiative transfer modelling which contribute to our knowledge of the plasma properties in eruptive prominences. We discuss in particular how these results, combined with observational data analysis, can help us in determining the plasma parameters in eruptive prominences.